Selective Transformation of Nickel‐Bound Formate to CO or C−C Coupling Products Triggered by Deprotonation and Steered by Alkali‐Metal Ions. (30th November 2020) - Zimmermann, Philipp; Ar, Deniz; Rößler, Marie; Holze, Patrick; Cula, Beatrice; Herwig, Christian; Limberg, Christian
Abstract: The complexes [L t Bu Ni(OCO‐ κ 2 O, C )]M3 [N(SiMe3 )2 ]2 (M=Li, Na, K), synthesized by deprotonation of a nickel formate complex [L t Bu NiOOCH] with the corresponding amides M[N(SiMe3 )2 ], feature a Ni II −CO2 2− core surrounded by Lewis‐acidic cations (M + ) and the influence of the latter on the behavior and reactivity was studied. The results point to a decrease of CO2 activation within the series Li, Na, and K, which is also reflected in the reactivity with Me3 SiOTf leading to the liberation of CO and formation of a Ni−OSiMe3 complex. Furthermore, in case of K +, the {[K3 [N(SiMe3 )2 ]2 } + shell around the Ni−CO2 2− entity was shown to have a large impact on its stabilization and behavior. If the number of K[N(SiMe3 )2 ] equivalents used in the reaction with [L t Bu NiOOCH] is decreased from 3 to 0.5, the deprotonated part of the precursor enters a complex reaction sequence with formation of [L t Bu Ni I (μ‐OOCH)Ni I L t Bu ]K and [L t Bu Ni(C2 O4 )NiL t Bu ]. The same reaction at higher concentrations additionally led to the formation of a unique hexanuclear Ni II complex containing both oxalate and mesoxalate ([O2 C‐CO2 ‐CO2 ] 4− ) ligands. Abstract : A deceptively simple proton abstraction from nickel‐bound formate not only prepares the resulting CO2 2− unit for the release of CO in contact with electrophiles but opens up unique complex reaction schemes including reduction of nickel(II) to nickel(I) and coupling of CO2 units to give oxalate and mesoxalate. Mesoxalate formation from individual CO2 units is so far unprecedented.